2-Azadienes as Enamine Umpolung Synthons for the Preparation of Chiral Amines - Malcolmson, Steven J.; Li, Kangnan; Shao, Xinxin (Synlett, 2019)
The development of new strategies for the preparation of chiral amines is an important objective in organic synthesis. In this Synpacts, we summarize our approach for catalytically accessing nucleophilic aminoalkyl metal species from 2-azadienes, and its application in generating a number of important but elusive chiral amine scaffolds. Reductive couplings with ketones and imines afford 1,2-amino tertiary alcohols and 1,2-diamines, respectively, whereas fluoroarylations of gem-difluoro-2-azadienes deliver α-trifluoromethylated benzylic amines.1 Introduction2 Background: Umpolung Strategies for Preparing Chiral Amines3 Background: 2-Azadienes4 Reductive Couplings of 2-Azadienes5 Fluoroarylations of gem-Difluoro-2-azadienes6 Summary and Outlook
Keywords: diamines; amino alcohols; 2-azadienes; reductive coupling; cross-coupling; fluoroarylation